2004
DOI: 10.1001/archpedi.158.10.1002
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Fall Injuries Among Infants

Abstract: Falls are a common cause of serious infant injuries, and nursery equipment is frequently involved in the injury-causing event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 22 publications
1
32
0
2
Order By: Relevance
“…Autores recomendam que os pais e responsáveis pelas crianças atentem para os riscos ambientais como tapetes soltos, pisos molhados, móveis com quinas, vidros, janelas sem proteção, berços sem proteção, camas elevadas, brinquedos espalhados, brinquedos pequenos que podem ser introduzidos como corpo estranho, objetos perfurocortantes, fogão, medicamentos e produtos de limpeza mal armazenados, animais domés-ticos 7,23 . De toda forma, é necessário enfatizar a importância da supervisão contínua de adultos, pais ou responsáveis, que devem estar atentos aos riscos, sem impedir o desenvolvimento das crianças, estimulando as descobertas e buscando sempre protegê-las dos riscos ambientais 24 .…”
Section: Discussionunclassified
“…Autores recomendam que os pais e responsáveis pelas crianças atentem para os riscos ambientais como tapetes soltos, pisos molhados, móveis com quinas, vidros, janelas sem proteção, berços sem proteção, camas elevadas, brinquedos espalhados, brinquedos pequenos que podem ser introduzidos como corpo estranho, objetos perfurocortantes, fogão, medicamentos e produtos de limpeza mal armazenados, animais domés-ticos 7,23 . De toda forma, é necessário enfatizar a importância da supervisão contínua de adultos, pais ou responsáveis, que devem estar atentos aos riscos, sem impedir o desenvolvimento das crianças, estimulando as descobertas e buscando sempre protegê-las dos riscos ambientais 24 .…”
Section: Discussionunclassified
“…50 Studies demonstrated a male predominance. 41,51,52 In the first year of life, falls are the most frequent type of injury. From 0 to 2 months of life, people carelessly let children fall; and between 3 and 11 months of life, falls from pieces of furniture are common.…”
Section: Fallsmentioning
confidence: 99%
“…The authors urge great caution with the changing table as it is responsible for falls associated with the highest frequency of hospital admissions. 51 Falls from windows are predominant among under-fiveyear-old male patients, possibly because these children are constantly driven by impulse, and lack the ability to recognize danger in a concrete manner. 52 As for the types of falls, the study by Gaspar showed that 34.2% occurred on the same level; followed by falls from buildings or other structures (13.8%); from stairs (11.7%); other falls from one level to another (9.1%); off the bed (8.6%); from trees (6.5%); from other type of furniture (5.6%); in addition to falls from the lap, from chairs and other types (10.5%).…”
Section: Fallsmentioning
confidence: 99%
“…A pesquisa de Agran et al, abrangendo crianças entre 0 e 3 anos, constatou que a taxa mais alta de agressões aconteceu no início da vida, ou seja, entre os lactentes de 0 a 5 meses de idade 37 51 .…”
Section: As Lesões Intencionais: Maus-tratos Contra Crianças E Adolesunclassified